Penyuluhan Kesehatan Reproduksi sebagai Upaya Pencegahan Seks Bebas Remaja Desa Gongseng Jombang - Rohmat Hidayat; M Farid Nasrullah; Faridl Darmawan; M Nur Latif; Ila Istiana; Hasna Mudzaqqiroh (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2023)
This community service activity in the form of adolescent reproductive health counseling aims to provide education about: (1) Health education regarding the effects that can be caused by free sex. (2) Health education regarding the phenomenon of early marriage in Indonesia. (3) Health education regarding the incidence of STDs and HIV/AIDS, ways of handling and efforts that can be made to prevent HIV/AIDS for adolescents. The program's target audience are Posyandu Remaja members consisting of 20 teenagers from the village of Gongseng Megaluh, Jombang. This activity was held on 12 October 2022 at the Gongseng Jombang Village Hall. The approach method used in this activity is the lecture method. Before the seminar starts, the team gives the seminar participants a copy of material on reproductive health in preventing free sex which will be delivered by the resource person. Then, after the delivery of the material, it was followed by a question and answer session to the seminar participants. This seminar activity was carried out as a form of problem solving from the partners. In this counseling, the participants were able to accept and master the material that had been presented, this was proven during the discussion where the participants always gave appropriate answers when asked questions by the presenters both orally and in writing. It is better for future counseling to allocate more time so that the results of the material that has been delivered can be reflected as a whole.